Modeling Defects, Shape Evolution, and Programmed Auto-Origami in Liquid Crystal Elastomers - Konya, Andrew; Gimenez-Pinto, Vianney; Selinger, Robin L. B. (Frontiers in Materials, 2016)
Liquid crystal elastomers represent a novel class of programmable shape-transforming materials whose shape change trajectory is encoded in the material’s nematic director field. Using three-dimensional nonlinear finite element elastodynamics simulation, we model a variety of different actuation geometries and device designs: thin films containing topological defects, patterns that induce formation of folds and twists, and a bas-relief structure. The inclusion of finite bending energy in the simulation model reveals features of actuation trajectory that may be absent when bending energy is neglected. We examine geometries with a director pattern uniform through the film thickness encoding multiple regions of positive Gaussian curvature. Simulations indicate that heating such a system uniformly produces a disordered state with curved regions emerging randomly in both directions due to the film’s up/down symmetry. By contrast, applying a thermal gradient by heating the material first on one side breaks up/down symmetry and results in a deterministic trajectory producing a more ordered final shape. We demonstrate that a folding zone design containing cut-out areas accommodates transverse displacements without warping or buckling; and demonstrate that bas-relief and more complex bent/twisted structures can be assembled by combining simple design motifs.